A rare case of tuberculous spinal arachnoiditis - Chaudhary, Suman; Chaurasia, Ankit; Mehrotra, Gunjan Kela; Arora, Kewalkishore; Patel, Yogesh (International Journal of Contemporary Pediatrics, 2018)
Central nervous system tuberculosis represents approximately 10% of extra pulmonary tuberculosis. However, spinal tuberculous arachnoiditis is a rare complication of CNS tuberculosis that can result in severe peripheral neurological deficit. We are reporting a case of 7-year-old male child of disseminated tuberculosis (pulmonary and spinal arachnoiditis) with nutritional anemia. We aim to illustrate the difficulties in the diagnosis and management of this potentially curable disease by reviewing the literature.